A participatory approach to developing a holistic and interdisciplinary adaptive capacity index for urban livelihoods - Davidson, Jaime (Department of Environmental and Geographical Science, 2017)
Evaluating the success of the growing number of climate adaptation initiatives is challenging. Assessment of adaptive capacity has been used to focus, prioritise and track the progress of adaptation interventions as well as to identify key barriers to and opportunities for implementing adaptation. Many adaptive capacity assessments have relied on secondary data and expert judgement. Given the call in climate change research and practice for bottom-up approaches that value communities' insight, it is clear that more participatory approaches for the assessment of adaptive capacity need to be developed. This research aims to address this gap by developing an adaptive capacity index that adopts a mixed methods approach and prioritises input from local stakeholders. Many adaptive capacity assessments have focussed on rural areas where livelihoods are directly exposed to climate variability. There is growing recognition that increasing numbers of people are settling in urban areas and many of these livelihoods are often at the margin. This thesis focuses on urban livelihoods where a more holistic understanding of adaptive capacity is required which recognises that a community's capacity to adjust to climatic stressors is interlinked to its capacity to adjust to environmental, social, economic and political challenges. An adaptive capacity index is developed in this thesis that includes and characterises the more subjective determinants of adaptive capacity, rather than giving precedence to material resources as the key determinant of a community's adaptive capacity. To achieve this richer understanding, the index is informed by a framework that incorporates aspects of individuals' agency and social cohesion. Using a case study of four towns in the Bergrivier Municipality, South Africa, this research develops an index of adaptive capacity that is holistic, collaborative and interdisciplinary. The scores generated by the index are analysed using statistical and regression analyses that are contextualised by stakeholders' inputs to explore the variation in adaptive capacity across socially differentiated groups. Key insights from these analyses relate to the variation in adaptive capacity between the four towns and differences in the adaptive capacity of males and females. Interestingly, the analyses revealed the absence of a positive correlation between schooling level and both adaptive capacity and wellbeing variables which could be attributed to limited economic opportunities in the area, particularly for high-skilled workers. The analyses also highlighted the need to support initiatives that strengthen the social cohesion within the community to improve the inclusion of marginal demographic groups. The thesis reflects on the participatory and collaborative research process, finding that combining quantitative and qualitative data through an interdisciplinary process has the potential to provide an index that is more reflective of subjective capacity. This more holistic understanding of adaptive capacity can align with the field of wellbeing, to offer valuable insight into building adaptive capacity for urban livelihoods that is grounded in both academic and applied fields.